URGENSI PENDIDIKAN AGAMA DALAM KELUARGA TERHADAP PEMBENTUKAN KEPRIBADIAN ANAK - H. Tahang, Jumri (Hunafa: Jurnal Studia Islamika, 2010)
One of the things that must be seriously paid attention according to Islamic teaching is education of the children. The two sources of Islamic teaching, the Qurâan and the hadith, convey many messages in order that the parents pay attention to religious teaching for their children. Within this context, the family constitutes the main pilar to form the personality of the children which must be conducted by implanting Islamic teaching since the early time. This is intended to encourage the children to possess good personality in order that they will not be easily influenced by a greater social life.Kata Kunci:Â Â Â  pendidikan agama, keluarga, Â kepribadian anak